Breakthrough Path of Low-Level Equilibrium of China's Policy-Oriented Financing Guarantee Market - Lv, Youqing; Ma, Guojian; Ding, Juan (Frontiers in Psychology, 2022)
Policy-oriented financing guarantee schemes are widely adopted in the world to alleviate the financing difficulties of small and medium-sized enterprises. However, the development level of policy-oriented financing guarantee market in China has not reached the desired high-level equilibrium target even though governments have issued a series of guiding policies. Accordingly, based on evolutionary game theory, this paper establishes and analyzes the game model between local governments, guarantee institutions and banks. Then, the breakthrough effects of different paths on the low-level equilibrium of the guarantee market are simulated. The results showed that strengthening superior government's performance appraisal intensity can only partially delay the "window period" of the low-level equilibrium. While adjusting local government's compensation coefficients or increasing banks' risk sharing ratio have further synergistic effects on the realization of the high-level equilibrium. Additionally, local governments' dynamic reward and penalty mechanism can effectively restrain the unbalanced state of financing guarantee market caused by banks' excess compensation risk, and finally impel the stabilization of the high-level equilibrium state.